Stopa zwrotu z kapitału własnego i marketing - Kłeczek, Ryszard (Return on Equity and Marketing, 2006)
Marketing decisions should create competitive advantage, but at the same time they can destroy Return on Equity (ROE). The author of the article tries to identify main marketing factors influencing sales profitability, asset turnover and, in consequence, ROE.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 119-125